RELEVANSI METODE GAME BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Budi Septiani, Tria (LPPM STAI Muhammadiyah Probolinggo, 2025)
Learning Islamic Religious Education has an important role in the formation of individual character and morals, but many educators still have difficulty in conveying Islamic Religious Education the core of the discussion of Islamic religious education as the basis for character formation. Until now, even the decline in student learning motivation in learning Islamic religious education requires special attention that matches the character of students and technological advances in the 21st century. Using a descriptive analytical approach, this study reviewed related literature and conducted case studies in several Islamic educational institutions. The results of the study indicate that GBL has great potential in increasing student learning motivation. This study also produces products in the form of educational games that can be used in learning Islamic Religious Education. The results of the study indicate that the educational games developed have the potential to increase student learning motivation and their understanding of religious concepts.